2005
DOI: 10.5575/geosoc.111.624
|View full text |Cite
|
Sign up to set email alerts
|

Lower Cretaceous radiolarian bedded chert from the Mineoka Belt, Boso Peninsula, Japan

Abstract: The Mineoka Belt is a complex fault zone composed of ophiolitic rocks and pelagic, hemipelagic and terrigenous sedimentary rocks, running from east-west in the south

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The Eurasian plate active margin including older accretionary mélange (Mineoka mélange) and forearc basin sediments (Shimanto Group) was covered by heterogeneous clastic sediments (Sakuma Group) during the mid-Miocene (c. 15 Ma), as indicated by the presence of the large foraminifer, Lepidocyclina sp. (Mori and Ogawa 2005;Ogawa and Sashida 2005;Ogawa et al 2008). Basic tuffaceous rocks that are interpreted to have been derived from the Izu-Bonin arc first appear in the Honshu forearc basin in the Boso Peninsula (Amatsu Formation) during the early late Miocene (13-12 Ma) Saito 1997, 1999).…”
Section: Constraints From the Geology Of Honshumentioning
confidence: 99%
“…The Eurasian plate active margin including older accretionary mélange (Mineoka mélange) and forearc basin sediments (Shimanto Group) was covered by heterogeneous clastic sediments (Sakuma Group) during the mid-Miocene (c. 15 Ma), as indicated by the presence of the large foraminifer, Lepidocyclina sp. (Mori and Ogawa 2005;Ogawa and Sashida 2005;Ogawa et al 2008). Basic tuffaceous rocks that are interpreted to have been derived from the Izu-Bonin arc first appear in the Honshu forearc basin in the Boso Peninsula (Amatsu Formation) during the early late Miocene (13-12 Ma) Saito 1997, 1999).…”
Section: Constraints From the Geology Of Honshumentioning
confidence: 99%
“…The fragments of oceanic crustal rock consist of pillow basalts, sheeted dolerite dikes, plutonic rocks, with minor pelagic to hemipelagic sedimentary rocks. Pelagic and hemipelagic sedimentary rocks show biostratigraphic ages are ranging from Late Albian radiolarian fossils in the Yo‐oka Beach of Kamogawa Harbor (Ogawa & Sashida, 2005), and from Paleocene to Miocene elsewhere (Mohiuddin & Ogawa, 1998; Takahashi, 1994).…”
Section: Geological Settingmentioning
confidence: 99%
“…Suzuki et al (1984) reported Late Eocene to Early Oligocene foramin-ifera fossils from the same formation. On the other hand, Ogawa and Sashida (2005) reported Middle Cretaceous radiolarian fossils from bedded chert from the Yoka Beach in Kamogawa City. The Hota Group is composed of coarse-grained volcaniclastic sandstone and tuffaceous mudstone to sandstone.…”
Section: Geological and Geochronological Overviewmentioning
confidence: 99%